THE ROLE AND IMPORTANCE OF FORMING CLINICAL THINKING IN MEDICAL STUDENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article addresses the issue of developing clinical thinking in medical university students in the context of modern requirements for medical education. It analyzes cognitive, pedagogical, and digital factors influencing the development of diagnostic and analytical abilities of future physicians. Special attention is given to empirical studies, innovative educational technologies (web quests, case method, interdisciplinary simulations), and the analysis of scientific publications from the Web of Science and Scopus databases. Promising research directions are identified, including neurocognitive mechanisms, the impact of molecular medicine, and the use of digital platforms. Practical recommendations are proposed for medical universities to implement systemic strategies for developing clinical thinking.